Alternative Photography as an Ethnographic Method - Flora Bartlett (Janeway JS, 2018)
In this article I discuss the creative potential of alternative photographic processes in anthropological research. I argue that an experimental, fine art approach to photography can be more effective in fieldwork than the ubiquitous documentary style favoured to illustrate ethnographic texts. Using my own early-stage research, I discuss the potential of using photograms, cyanotypes, and archival images. I discuss the potential of these forms for multimedia interventions, through the inclusion of text into the physical image-objects themselves. This approach to visual methodologies challenges the positioning of the researcher to their participants and allows collaboration and creative engagement in the field. It connects visual practice with phenomenological approaches to experience.